(3GdGSJjYGH aj eYQaI GdCUMGHs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s ((3EOQjS Hf eMeO Hf EOQjS Hf jMji Hf MeRI s)
(3ChdgG (B:s
(3jHOC HJQLeI WdjH Hf CRgQ Hf YHO Yha GdbQTi GdRgQi s
(3BNQgG (B:s
(3jfJgi HJQLeI YHGOI Hf Chai GdfeQi s
(3LGA HBNQ GdfSNI (B:(3W HdZ ebGHdI Ydi fSNI ZjQ ebGHdI adjYde Pdc ef WGdYg (B"s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ GdZQHjI (B((3JGQjN (B3) s
Keywords: (3GdJGQjNs